Effects of oxytocin receptor ligands on anxiogenic-like effect, social avoidance and changes on medial prefrontal cortex oxytocin receptor expression evoked by chronic social defeat stress in rats - Canto-de-Souza, Lucas [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Busnardo, Cristiane [UNESP]; Crestani, Carlos C [UNESP] (Elsevier, 2025)
We investigated the effect of systemic administration of the synthetic oxytocin (OXT) analog carbetocin and/or OXT receptor antagonists (atosiban and L-368,899) on social avoidance and anxiogenic-like effect in male rats subjected to chronic social defeat stress (cSDS). Effect of cSDS and pharmacological manipulation of OXT system on expression of OXT receptor within the medial prefrontal cortex (mPFC) subregions [anterior cingulate (Cg), prelimbic (PL) and infralimbic (IL) cortices] was also evaluated. Our behavioral results indicated that cSDS, while not inducing social avoidance in the social interaction test, reliably induced anxiogenic-like effect as measured by the elevated plus maze test. Chronic systemic treatment with either carbetocin or atosiban, but not L-368,899, during cSDS protocol dose-dependently prevented the anxiogenic-like effect. Both atosiban and L-368,899 inhibited the anxiolytic effect of carbetocin in defeated animals, confirming OXT receptor-mediated effect. Also, cSDS increased OXT receptor levels within the Cg, which was inhibited by both atosiban and L-368,899 treatments. Conversely, cSDS did not affect OXT receptor within the PL and IL. However, carbetocin treatment increased OXT receptor expression within the PL and IL of defeated animals, an effect that was blocked by either atosiban or L-368,899. Taken together, our study provides evidence for the critical role of the OXT system and its pharmacological manipulation in modulating anxiogenic-like effects evoked by social stress. Furthermore, the region-specific modulation of OXT receptor expression within the mPFC by stress and OXT system pharmacological manipulation emphasize the complex and dynamic nature of OXT receptor regulation in brain regions crucial for emotional processing.